Selected papers from the 46th Linguistic Symposium on Romance Languages (LSRL), Stony Brook, NY - Repetti, Lori; Ordoñez, Francisco, 1967- (Romance Languages and Linguistic Theory ;, 2018)
"This book contains a peer-reviewed selection of papers presented at the 46th Linguistic Symposium on Romance Languages (LSRL 46) that took place in April 2016 at Stony Brook University (SUNY), New York. The most current research and debates on bilingualism, historical linguistics, morphology, phonology, semantics, sociolinguistics, and syntax can be found in its pages. This collection will be of interest to Romance linguists and general linguists as well"--